2022
DOI: 10.1039/d2dt02166h
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a Mg2+-containing MOF through ion exchange and its high ionic conductivity

Abstract: We first report on preparation and ionic conductivity of a Mg2+-included metal–organic framework (MOF) having Type A feature, i.e., anionic framework including Mg2+ as counter cations. We prepared Mg3[(MnMo6O18)2L] (L12–...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…4 shows the temperature dependence of ionic conductivity under various guest vapors of small organic molecules or dry N 2 . As with a previous report (MOF-688-Mg), 9 SU-102-Mg exhibited insulating character under dry N 2 , clearly indicating that Mg 2+ located in the pores are strongly bound by the framework and thus cannot be migrated. Conversely, small guest molecules such as MeOH and MeCN drastically enhance its ionic conductivity.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…4 shows the temperature dependence of ionic conductivity under various guest vapors of small organic molecules or dry N 2 . As with a previous report (MOF-688-Mg), 9 SU-102-Mg exhibited insulating character under dry N 2 , clearly indicating that Mg 2+ located in the pores are strongly bound by the framework and thus cannot be migrated. Conversely, small guest molecules such as MeOH and MeCN drastically enhance its ionic conductivity.…”
supporting
confidence: 90%
“…The result suggested that the crystalline pores or regular channels of SU-102-Mg deeply contribute to the efficient migration of the included Mg 2+ . As listed in Table S1, † the activation energy of SU-102-Mg under each guest is also similar to that of MOF-688-Mg, 9 suggesting the similar conducting mechanisms under the guest vapors.…”
mentioning
confidence: 66%
See 1 more Smart Citation